Correction: Nursing staff's attitudes towards the prevention of adverse events among hospitalized people with dementia: Protocol of qualitative systematic review and evidence synthesis. - Lucía Catalán; Anne Margriet Pot; Amy Pepper; Karen Harrison Dening; Déborah Oliveira (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0301651.].